2020
DOI: 10.3390/ijms21072507
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Sensory Nerve Function by Insulin: Possible Relevance to Pain, Inflammation and Axon Growth

Abstract: Insulin, besides its pivotal role in energy metabolism, may also modulate neuronal processes through acting on insulin receptors (InsRs) expressed by neurons of both the central and the peripheral nervous system. Recently, the distribution and functional significance of InsRs localized on a subset of multifunctional primary sensory neurons (PSNs) have been revealed. Systematic investigations into the cellular electrophysiology, neurochemistry and morphological traits of InsR-expressing PSNs indicated complex f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 147 publications
1
5
0
Order By: Relevance
“…However, we found that the expression of SP decreased in HFD-STZ-induced T2DM rats as the islets showed ill-conditioned patterns. This conclusion is consistent with Razavi’s assertion [ 75 ]. SP is one of the vital sources of pancreatic duct proliferation [ 76 ].…”
Section: Discussionsupporting
confidence: 93%
“…However, we found that the expression of SP decreased in HFD-STZ-induced T2DM rats as the islets showed ill-conditioned patterns. This conclusion is consistent with Razavi’s assertion [ 75 ]. SP is one of the vital sources of pancreatic duct proliferation [ 76 ].…”
Section: Discussionsupporting
confidence: 93%
“…However, there is increasing evidence showing neurotrophic, neuromodulatory, and neuroendocrine activity, as well as synaptic plasticity and effects on neurotransmitter release, particularly monoamines (Gasparini et al., 2002; Gerozissis, 2003; Gispen & Biessels, 2000). In addition to its central role, insulin may also modulate neuronal processes in the CNS (Lázár et al., 2020). Molecular mechanisms might contribute to the pathophysiology of diabetic neuropathy and pain (Misawa et al., 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Anti-NGF monoclonal antibodies (TrkA receptor in-hibitors) have shown promise in treating pain and are currently in clinical trials, but a small subset of patients develop rapidly progressive joint degeneration [89]. RET, FGFR1, KIT, InsR, and PDGFRβ are among the other receptors associated with pain modulation within DRGs [90][91][92][93][94], and the understanding of the subtypes of neurons expressing each of these receptors and the spatiotemporal relationship between them driving MAPK in DRGs remains to be elucidated. CRISPR has shown promise as a technique for effectively studying and modulating the epigenome of primary cultured DRGs with a 75% success rate [95].…”
Section: Pain Signalingmentioning
confidence: 99%